BRONJ-related jaw bone is associated with increased Dlx-5 and suppressed osteopontin-implication in the site-specific alteration of angiogenesis and bone turnover by bisphosphonates - Wehrhan, Falk; Amann, Kerstin Ute; Moebius, Patrick; Weber, Manuel; Preidl, Raimund; Ries, Jutta; Stockmann, Philipp (Clinical Oral Investigations, 2015)
Site-specific suppression of bone remodelling has been implicated in bisphosphonate-(BP)-related osteonecrosis of the jaws (BRONJ). Due to the origin of jaw bone from cranial neural crest, osseous differentiation is regulated specifically by the antagonizing BMP-2-downstream-transcription factors Msx-1 and Dlx-5. Osteopontin has been implicated in bone remodelling and angiogenesis. The osteoblast and osteoclast progenitor proliferation mediating Msx-1 has been demonstrated to be suppressed in BRONJ. In vitro BPs were shown to increase Dlx-5 and to suppress osteopontin expression. This study targeted Dlx-5 and osteopontin in BRONJ-related and BP-exposed jaw bone compared with healthy jaw bone samples at protein- and messenger RNA (mRNA) level, since increased Dlx-5 and suppressed osteopontin might account for impaired bone turnover in BRONJ.Fifteen BRONJ-exposed, 15 BP-exposed and 20 healthy jaw bone samples were processed for real-time reverse transcription polymerase chain reaction (RT-PCR) and for immunohistochemistry. Targeting Dlx-5, osteopontin and glyceraldehyde 3-phosphate dehydrogenase mRNA was extracted, quantified by the LabChip-method, followed by quantitative RT-PCR. For immunohistochemistry, an autostaining-based alkaline phosphatase antialkaline phosphatase (APAPP) staining kit was used. Semiquantitative assessment was performed measuring the ratio of stained cells/total number of cells (labelling index, Bonferroni adjustment).The labelling index was significant decreased for osteopontin (p < 0.017) and significantly increased for Dlx-5 (p < 0.021) in BRONJ samples. In BRONJ specimens, a significant fivefold decrease in gene expression for osteopontin (p < 0.015) and a significant eightfold increase in Dlx-5 expression (p < 0.012) were found.BRONJ-related suppression of bone turnover is consistent with increased Dlx-5 expression and with suppression of osteopontin. The BP-related impaired BMP-2-Msx-1-Dlx-5 axis might explain the jaw bone specific alteration by BP.The findings of this study help to explain the restriction of RONJ to craniofacial bones. BRONJ might serve as a model of disease elucidating the specific signal transduction of neural crest cell-derived bone structures in health and disease.
EVALuna2:24383

Diabetes mellitus negatively affects peri-implant bone formation in the diabetic domestic pig - von Wilmowsky, Cornelius; Stockmann, Philipp; Harsch, Igor; Amann, Kerstin Ute; Metzler, Philipp; Lutz, Rainer; Möst, Tobias; Neukam, Friedrich Wilhelm; Schlegel, Karl Andreas (Journal of Clinical Periodontology, 2011)
Aim: Diabetes mellitus is classified as a relative contraindication for implant treatment, and higher failure rates have been seen in diabetic patients. The aim of the present study was to investigate the effect of diabetes on peri-implant bone formation in an animal model of human bone repair. Materials and Methods: Diabetes was induced by an intra-venous application of streptozotocin (90 mg/kg) in 15 domestic pigs. Implants were placed after significant histopathological changes in the hard and soft tissues were verified. The bone-implant contact (BIC), peri-implant bone mineral density (BMD), and expression of collagen type-I and osteocalcin proteins were qualitatively evaluated 4 and 12 weeks after implantation. Fifteen animals served as healthy controls. Results: Diabetes caused pathological changes in the soft and hard tissues. The BIC and BMD were significantly reduced in the diabetic group after 4 and 12 weeks. Collagen type-I was increased in the diabetic group at both time points, whereas osteocalcin was reduced in the diabetic group. Conclusions: Poorly controlled diabetes negatively affects peri-implant bone formation and bone mineralization. These findings have to be taken into consideration for diabetic patients with an indication for implant therapy. © 2011 John Wiley & Sons A/S.
CRIS-Team Scopus Importer:2024-05-13
Keywords: bone; diabetes; implants; osseointegration; pig

Fulminant course of osteonecrosis of the jaw in a rheumatoid arthritis patient following oral bisphosphonate intake and biologic therapy - Ebker, Tobias; Rech, Jürgen; von Wilmowsky, Cornelius; Neukam, Friedrich Wilhelm; Stockmann, Philipp (Rheumatology, 2013)
CRIS-Team Scopus Importer:2021-02-03

Immunohistological expression of human ß-defensin-1 and human ß-defensin-2 in exacerbation of acute and secondary chronic osteomyelitis of the mandible - Beck-Broichsitter, Benedicta E.; Dau, Heino; Moest, Tobias; Jochens, Arne; Stockmann, Philipp; Wiltfang, Joerg; Becker, Stephan T. (Journal of Oral Pathology & Medicine, 2015)
The majority of patients diagnosed with osteomyelitis of the jaw have severe complaints. Unfortunately, the pathogenesis still remains unclear. Human ß-defensins expressed in epithelial and bone tissues as a part of the innate immunity may be involved in disease development. In this study, we hypothesize that expression levels of human ß-defensin-1 and -2 in the acute and secondary chronic osteomyelitis may be altered in comparison with healthy bone and with bisphosphonate-associated necrosis as well as irradiation from a previous study.Bone samples were collected during surgical debridement in a total of eight patients suffering from acute or secondary chronic osteomyelitis of the jaw. Expression levels of hBD-1 and -2 were quantified and related to non-stained cells. Ratios were compared by one-way ANOVA and multiple tests by Holm-Bonferroni.Multiple testing revealed no significant differences for expression levels of human ß-defensin-1 between all groups, whereas labeling index of human ß-defensin-2 was significantly different between specimens of bisphosphonate-associated osteonecrosis of the jaws and all other groups. No significant difference occurred between samples of floride osteomyelitis and healthy bone for expression of hBD-1 and -2.Although the affected patients showed all clinical signs of acute inflammation, expression levels in acute and secondary chronic osteomyelitis in the jaws did not reveal statistically significant differences compared with healthy bone samples. The weak immunological host response in terms of a putative genetically predisposition should be further discussed as pathogenesis factor for osteomyelitis in the future.
EVALuna2:24392

Osteonecrosis of the jaw in a Crohn's disease patient following a course of Bisphosphonate and Adalimumab therapy: a case report - Preidl, Raimund; Ebker, Tobias; Raithel, Martin; Wehrhan, Falk; Neukam, Friedrich Wilhelm; Stockmann, Philipp (BMC Gastroenterology, 2014)
Bisphosphonates have a widespread indication for osteoporosis and are also applied in cancer patients with skeletal-related conditions. Bisphosphonate-associated osteonecrosis of the jaw (BRONJ) is a feared side effect which is hard to treat and often affects patient´s quality of life in an extensive manner. Adalimumab (Humira®), a fully human recombinant antibody specific for tumor necrosis factor- ?, is approved for treatment in patients with Inflammatory Bowel Disease like ulcerative colitis or Crohn's disease.In March 2013, a 36-year-old female presented with right-sided perimandibular swelling, recurrent facial pain and exposed necrotic bone after previous extraction of tooth 47. She had the medical history of Crohn's disease for more than one decade with chronic active enterocolitis, fistula disease as well as previous oral manifestation and was currently treated with Adalimumab since September 2008. Due to steroid-induced osteoporosis, diagnosed in 2004, she received oral Bisphosphonates (Risedronate) from 2004 until 2007 followed by two infusions of Zoledronic acid in 2008 and 2009.This patient with a medical history of Crohn's disease and gastrointestinal remission under Adalimumab therapy presented with osteonecrosis of the jaw after suspended oral and intravenous Bisphosphonate therapy implicating that the biologic therapy with an anti-TNF-? antibody might promote the manifestation of osteonecrosis and compromise oral healing capacity.
EVALuna2:1730

Osteo-radio-necrosis (ORN) and bisphosphonate-related osteonecrosis of the jaws (BRONJ): the histopathological differences under the clinical similarities - Mitsimponas, Konstantinos; Moebius, Patrick; Amann, Kerstin Ute; Stockmann, Philipp; Schlegel, Karl-Andreas; Neukam, Friedrich Wilhelm; Wehrhan, Falk (International Journal of Clinical and Experimental Pathology, 2014)
Both Osteoradionecrosis (ORN) and Bisphosphonate associated osteonecrosis of the jaws (BRONJ) present clinically as regions of exposed necrotic bone. The study aimed to demonstrate the histopathological differences behind the observed clinical similarities.Ten ORN specimens and ten BRONJ specimens were used, as well as ten samples of normal mandibular bone as control. Two bone-specific stainings were used, i.e. Sirius Red for the study of the relative presence of collagen types I and III and toluidine blue for the study the osteon density.The Red Green Blue (RGB)-analysis of the specimens stained with Sirius Red identified significant differences between the chromatic patterns observed in bone preparations of patients suffering from ORN when compared to both BRONJ and control samples. Moreover, the osteon density of the BRONJ samples was significantly lower when compared to ORN and normal bone samples.The demonstrated differences in the bone architecture and in the bone collagen content between the two pathological conditions most likely reflect underlying pathophysiological differences.
EVALuna2:24379

Perioperative factors that influence the outcome of microsurgical reconstructions in craniomaxillofacial surgery - Preidl, Raimund; Wehrhan, Falk; Schlittenbauer, T.; Neukam, Friedrich Wilhelm; Stockmann, Philipp (British Journal of Oral and Maxillofacial Surgery, 2015)
Microsurgical tissue transfer is a well-established way of reconstructing the head and neck, but there are still many postoperative complications that require revision. The aim of this study was to clarify perioperative factors and characteristics of patients that influence the success of the flap and the need for revision. We retrospectively studied 368 patients who were treated with microsurgical free tissue transfer in the head and neck area at the Department of Oral and Maxillofacial Surgery at the University Medical Centre, Erlangen, between 2004 and 2009. Investigations concentrated on patients' characteristics and operative factors. Free scapular or parascapular flaps (n=161, 44%) and radial forearm flaps (n=119, 32%) were predominantly used for the reconstruction of major defects in the mandible and the floor of the mouth. In 39 patients (11%) revision was required, which resulted in a success rate of 96%. There was a significant association between preoperative American Society of Anesthesiologists (ASA) grade and postoperative survival of the flap (p=0.04). Patients previously treated by irradiation required significantly more revisions than those not so treated (p=0.04). The use of vein grafts was also significantly associated with the need for revision (p=0.02). The ASA grade influenced the success rate but was not associated with the number of revisions. These factors must be taken into consideration when intervention is planned to reduce the number of postoperative complications and interventions further.
EVALuna2:24398

Saliva diagnostics in patients suffering from bisphosphonate-associated osteonecrosis of the jaw: Results of an observational study - Stockmann, Philipp; Ebker, Tobias; Bergauer, Jasmin; Wehrhan, Falk (Journal of Cranio-Maxillofacial Surgery, 2020)
Objective: One of the severe side effects of bisphosphonate (BP) therapy is bisphosphonate-associated osteonecrosis of the jaw (BONJ). However, there is no information available about its pathogenesis. Hence, the aim of this observational study was to contribute to discerning this pathogenesis by comparing salivary quantity and quality in patients with BONJ and undergoing BP treatment. Materials and methods: This study included 60 patients divided into three groups. The first group consisted of 20 patients with established BONJ, the second group had 20 patients undergoing BP treatment, and the third group comprised 20 healthy individuals. These groups were analysed for the flow rate of stimulated saliva, buffer capacity, and salivary pH level. Results: Reduced salivation was observed in a significantly high number of patients with established BONJ (n = 8) and those undergoing BP treatment (n = 9) in comparison with the healthy control group (n = 4; p = 0.039). Though the distribution of the mean value of stimulated saliva flow rates in patients undergoing BP treatment was lower than in the control group, the difference was not significant. Moreover, there were no significant differences in the salivary pH level and buffer capacity in patients undergoing BP treatment as compared with the healthy control group. Conclusions: It is possible that the quantity of human saliva is affected by BP treatment. This reduction in saliva production could have a negative effect on mucosal health and is perhaps a cofactor in the pathogenesis of BONJ.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Bisphosphonates; Medication-related osteonecrosis; Pathogenesis; Saliva

Sinus floor augmentation with autogenous bone vs. a bovine-derived xenograft - a 5-year retrospective study - Lutz, Rainer; Berger-Fink, Susanne; Stockmann, Philipp; Neukam, Friedrich Wilhelm; Schlegel, Karl Andreas (Clinical Oral Implants Research, 2015)
The long-term outcome after sinus augmentation with autogenous bone or a bovine xenograft (Bio-Oss(®)) was assessed in 47 patients. Inclusion criterion was a vertical dimension of the maxilla of <4 mm. After a functional loading period of 60 months, implant survival and reduction in the augmentation height were compared between the two groups evaluated.Sinus augmentation was performed using mandibular bone grafts or Bio-Oss(®). In the autogenous bone group, 70 implants were placed in 23 patients, while in the Bio-Oss(®) group, 24 patients received 98 implants. Fisher's exact test and equivalence testing were used to compare implant survival rates.The overall survival rate of the implants was 95.8% 5 years after implant insertion. In the autogenous bone group, the implants had a survival rate of 97.1%, while in the Bio-Oss(®) group, 94.9% of the implants survived. The difference was not statistically significant (P > 0.05); both treatments are equivalent (confidence interval 90%) for the equivalence interval [-0.1; 0.1]. 43.5% of the cases showed no reduction in the augmentation height 5 years after implant insertion, when augmentation was performed with autogenous bone, while in the Bio-Oss(®) group, no resorption was found in 50% of the augmented areas. Up to 25% reduction in augmentation height was found in 47.8% in the autogenous and in 45.8% in the Bio-Oss(®) group. In 8.7% of all cases in the autogenous bone group and in 4.2 % in the Bio-Oss(®) group, up to 50% of the augmented height was resorbed.After a 5 years evaluation period, Bio-Oss(®) as material for the indication maxillary sinus augmentation shows to be equivalent to autogenous bone grafting.
EVALuna2:24395

The effect of load on heat production, thermal effects and expenditure of time during implant site preparation - an experimental ex vivo comparison between piezosurgery and conventional drilling - Stelzle, Florian; Frenkel, Carsten; Riemann, Max; Knipfer, Christian; Stockmann, Philipp; Nkenke, Emeka (Clinical Oral Implants Research, 2014)
Piezoelectric surgery (PS) is meant to be a gentle osteotomy method. The aim of this study was to compare piezosurgical vs. conventional drilling methods for implant site preparation (ISP) - focusing on load-dependent thermal effect on hard tissue and the expenditure of ISP time.Three hundred and sixty ISP were performed on ex vivo pig heads using piezosurgery, spiral burs (SB) and trephine burs (TB). The load applied was increased from 0 to 1000 g in 100-g intervals. Temperature within the bone was measured with a thermocouple, and duration was recorded with a stop watch. Thermal effects were histomorphometrically analysed. Twelve ISPs per technique were performed at the lateral wall of the maxillary sinus.PS yields the highest mean temperatures (48.6 ± 3.4°C) and thermal effects (200.7 ± 44.4 ?m), both at 900-1000 g. Duration is reduced with a plus of load and significantly longer in either case for PS (P < 0.05). There is a correlation of the applied load with all other examined factors for PS and TB. Temperature and histological effects decrease for SB beyond 500 g.PS yields significantly higher temperatures and thermal tissue alterations on load levels higher than 500 g and is significantly slower for ISP compared to SB and TB. For ISP with PS, a maximum load of 400 g should be maintained.
EVALuna2:24343

The free scapular/parascapular flap as a reliable method of reconstruction in the head and neck region: a retrospective analysis of 130 reconstructions performed over a period of 5 years in a single department - Mitsimponas, Konstantinos; Iliopoulos, Christos; Stockmann, Philipp; Bumiller, Lars; Nkenke, Emeka; Neukam, Friedrich Wilhelm; Schlegel, Karl-Andreas (Journal of Cranio-Maxillofacial Surgery, 2014)
The scapular/parascapular free flap was described by Saijo in 1978 and has since then been widely used in reconstructive procedures.This is a retrospective study, describing our experience with the use of free scapula/parascapular flap in 130 reconstructions over a period of 5 years in the Department of Oral and Maxillofacial Surgery of the University Hospital of Erlangen. Demographical data, data regarding the underlying pathology, flap raising details, microvascular anastomoses, early and late postoperative complications will be presented.The flap was raised without problems and the donor site was primarily closed in all cases. Sixteen flaps required revision. Five transplants were lost (failure rate of 3.85%). Loss of part of the flap was observed in 3 cases (2.3%).The free scapula/parascapular flap is a versatile and reliable flap that can find many applications in the reconstruction of complex head and neck defects.
EVALuna2:24359

The outcome after surgical therapy of bisphosphonate-associated osteonecrosis of the jaw–results of a clinical case series with an average follow-up of 20 months - Stockmann, Philipp; Burger, Moritz; von Wilmowsky, Cornelius; Ebker, Tobias; Lutz, Rainer; Bauersachs, Anne; Nkenke, Emeka; Neukam, Friedrich Wilhelm; Wehrhan, Falk (Clinical Oral Investigations, 2014)
The present case series evaluates the success rate of osteotomy and primary wound closure in patients with bisphosphonate-associated osteonecrosis of the jaw (BRONJ).Eighty patients suffering from BRONJ were included in the study. All patients received intravenous bisphosphonate therapy and underwent osteotomy and primary wound closure according to a standardised protocol. After discharge, the patients were reviewed on a regular basis over an average time period of 20 months.During follow-up in 11 patients, a recurrence of BRONJ occurred in the former operation field. Seventeen patients died due to their underlying disease. The success rate of osteotomy and primary wound closure in the treatment of BRONJ was calculated at 84.2 % 20 months after surgery. The results showed non-significant difference concerning the outcome of surgery in the different clinical stages of BRONJ.In accordance with previous studies, stage-independent osteotomy and primary wound closure combined with antibiotics shall be deemed a viable treatment option in patients suffering from BRONJ.With a high success rate, osteotomy in combination with primary wound closure seems to be a viable alternative to more conservative protocols in the treatment of BRONJ.
EVALuna2:24358